2016
DOI: 10.11611/jmer819
|View full text |Cite
|
Sign up to set email alerts
|

Ki̇şi̇-Çevre Uyumu Ve Takim Çalişmasi İşlevsi̇zli̇ği̇ İli̇şki̇si̇nde Ahlâki̇ Çözülme’ni̇n Araci Rolü

Abstract: THE MEDIATING ROLE OF MORAL DISENGAGEMENT IN THE RELATIONSHIP BETWEEN PERSON-ENVIRONMENT FIT AND TEAMWORK DYSFUNCTIONING ABSTARCT The interest in having moral standards, which is promoted as the differentiation strategy of businesses and what makes them to reach successful outcomes, requires the mutual commitment of employees and managers to the moral standards. The attitude of connivance and breach of moral standards disconcert the organization and weakens the feeling of trust among employees and thus is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…An examination of the scales related to moral disengagement in Turkey revealed that there were measurement tools for measuring traditional moral disengagement. For instance, there are Turkish versions of the Moral Disengagement Scale [39] for the purpose of determining the traditional moral disengagement levels of adults and the Collective Moral Disengagement Scale [40] for the determination of the collective moral disengagement levels of adolescents. However, no scale has been developed for determining moral disengagement behavior in online environments.…”
Section: Present Studymentioning
confidence: 99%
“…An examination of the scales related to moral disengagement in Turkey revealed that there were measurement tools for measuring traditional moral disengagement. For instance, there are Turkish versions of the Moral Disengagement Scale [39] for the purpose of determining the traditional moral disengagement levels of adults and the Collective Moral Disengagement Scale [40] for the determination of the collective moral disengagement levels of adolescents. However, no scale has been developed for determining moral disengagement behavior in online environments.…”
Section: Present Studymentioning
confidence: 99%
“…In the literature especially in recent years, studies on moral disengagement (Boardley and Kavussanu;Çelik, 2022;Detert et al 2008;Erbaş and Şahin-Perçin, 2016;Eroğlu et al 2020;Fitzpatrick and Bussey, 2018;Gencer, 2020;Hacıkeleşoğlu, 2021;Kağan and Yazıcıoğlu, 2021;Karataş et al 2019;Keskin, 2021;Köfünyeli, 2022;Köklü, 2019;Newman et al 2017;Nur, 2019;Özkan, 2019;Parladıcı, 2020;Sayraç-Kavadar, 2021;Turan, 2021;Visconti et al 2015;Yazıcıoğlu, 2020;Yavuz-Birben, 2019), the issue of academic motivation (Alkan and Arslan, 2019;Arslantaş, 2021;Bilgili and Keklik, 2022;Canbay, 2016;Gürlek, 2021;Kıran, 2019;Kiremitci et al 2020;Koca and Dadandı, 2019;Özgenel and Deniz, 2020;Selen, 2022;Taskesen, 2019;Taşkın, 2016;Tezel, 2021;Titrek et al 2018;Yeşiltaş, 2020) and the studies examining the relationship between the two concepts are not at sufficient level. In the current study, studies similar to the subject area content of the research problem were examined in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Kişi-çevre uyumu, bireyin çalışma ortamındaki birden fazla sistemle uyumluluğunu içeren kapsamlı bir kavramdır (Kristof-Brown vd., 2002). Kişi-çevre uyumu bakış açısı altında kişi-meslek, kişi-örgüt, kişi-iş, kişi-yönetici ve kişi-grup uyumu gibi farklı uyum türleri ele alınmaktadır (Kristof, 1996;Irak, 2012;Erbaş ve Şahin Perçin, 2016;Gürlek, 2019). Bir çok araştırma kişi-çevre uyumunun iş tatmini, (Nguyen ve Borteyrou, 2016), iş performansı (Kieffer vd., 2004) ve örgütsel bağlılık (Astakhova, 2016) gibi temel örgütsel davranış değişkenlerinin güçlü bir belirleyicisi olduğunu ortaya koymuştur.…”
Section: Introductionunclassified